New species of Anastrepha (Diptera: Tephritidae), with a key for the species of the megacantha clade - Norrbom, Allen L.; Korytkowski, Cheslavo A. (Zootaxa, 2012)
Thirteen new species of Anastrepha are described and illustrated: A. anopla (Brazil, Ecuador), A. grandicarina (Brazil,Ecuador, Perú), A. hadracantha (Ecuador), A. haplacantha (Ecuador), A. hyperacantha (Ecuador), A. inaequalis (Trini-dad), A. intermedia (Panamá), A. lopezi (Guatemala), A. macracantha (Ecuador), A. magnicurva (Ecuador, Perú), A. neo-gigantea (Ecuador, Venezuela), A. peneramosa (Perú), and A. stangei (Venezuela). A key for the species of the megacantha clade is provided. Pouteria buenaventurensis (Sapotaceae) is reported as a host plant for A. intermedia.